The Effect of Organizational Culture and Job Satisfaction on Work Motivation of Industry and Trade Service Employees in Sungai Penuh City - Efrianto, Efrianto; Hendra, Hendra; Kartawijaya, Sukarta (Kirana Publisher (KNPub), 2023)
A factor that cannot be ignored in improving employee performance is motivation. This is according to Hasibuan's opinion (1996: 45) an employee will produce performance high if employees are motivated at work. Motivation can be a driving force someone carries out an activity in order to get the best results. Therefore it is not surprising that employees who have high work motivation usually also have high performance. Another factor which cannot be ignored Improving employee performance is an